До проблеми розпізнавання поховань чорногорівської групи - Отрощенко, В.В. (Археологія і давня історія України, 2019)
Статтю присвячено питанням формування та поповнення джерельної бази чорногорівської групи поховань. Розглянутий каталог кіммерійських поховань, створений С. В. Махортих (2005), запропоновані підходи до його удосконалення та очищення від комплексів доби фінальної бронзи та артефактів з пам'яток осілого населення кіммерійської доби. Звернено увагу на нерозпізнані досі комплекси чорногорівсько групи через помилкову культуру атрибуцію їх. The article deals with the questions of formation and replenishment of the Chornohorivska group of monuments source base of the IX—VIII c. BC. The catalog of Cimmerian burials, created by S. V. Makhortykh (2005), was analyzed. Due to the discussion points of its configuration, it is proposed to improve this register. It is advisable to clear the catalog from the complexes of the Bilozerska culture of the of the Final Bronze Age and artifacts from the monuments of the settled population — the Cimmerian neighbors. Attention is paid to the still unrecognized complexes of the Chornohorivska group, defined earlier as the cultures of the Bronze Age. The approaches to the cultural identification of the non-inventory burials of this group of the Cimmerian population are marked. It was noticed that instead of the «fetal» position of the dead during the Late and Final Bronze, among nomads (Chornohorivska group population) in the early Iron Age the «horseman» buried position was recorded.